2020
DOI: 10.1016/j.ctrv.2020.102069
|View full text |Cite
|
Sign up to set email alerts
|

Systemic therapy in the management of recurrent or metastatic salivary duct carcinoma: A systematic review

Abstract: Background: Salivary duct carcinoma (SDC) is an aggressive subtype of salivary gland cancer. Approximately half of SDC patients will develop recurrences or metastases. Therapeutic palliative therapy is therefore often needed. The majority of SDC tumors expresses the androgen receptor (AR) and one-third expresses human epidermal growth factor receptor 2 (HER2), both are potential therapeutic targets. The aim of this paper is to systematically review and summarize the evidence on systemic palliative therapy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 86 publications
(146 reference statements)
3
49
0
Order By: Relevance
“…In contrast, ICIs might be tried in patients with SGC without targetable molecules instead of conventional cytotoxic anticancer agents. Recent studies reported that cytotoxic anticancer agents seemed to achieve a higher ORR with higher toxicity than the ICIs 3,4,24,25 . However, it is difficult to directly compare those therapies as patient background (e.g., histological type) might differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ICIs might be tried in patients with SGC without targetable molecules instead of conventional cytotoxic anticancer agents. Recent studies reported that cytotoxic anticancer agents seemed to achieve a higher ORR with higher toxicity than the ICIs 3,4,24,25 . However, it is difficult to directly compare those therapies as patient background (e.g., histological type) might differ.…”
Section: Discussionmentioning
confidence: 99%
“…recommended for patients at a high risk of recurrence 3 . Numerous clinical trials of cytotoxic chemotherapies have been conducted in patients with recurrent and/or metastatic (R/M) SGC 3,4 and several potential targets for systemic therapy have been reported [5][6][7][8][9][10][11][12][13][14][15][16][17] ; however, there were no randomised controlled trials 3,4 . Moreover, unlike lung metastasis of adenoid cystic carcinoma (AdCC), majority of which show indolent growth 3,18,19 , the progression of salivary duct carcinoma (SDC) and adenocarcinoma, not otherwise specified (NOS) is aggressive 3,20,21 .…”
mentioning
confidence: 99%
“… 11 A nationwide case series involving 35 patients with AR-positive aSDC treated with either monotherapy (luteinizing hormone-releasing hormone analogues or the AR antagonists: enzalutamide or bicalutamide) or combined androgen blockade (luteinizing hormone-releasing hormone analogue and bicalutamide) had a clinical benefit rate of 50%. 10 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…This includes mutations in TP53 (53-68%), PIK3CA (18-26%), HRAS (16-23%), BRAF (4%) and AKT1 (1.5%). Reports on the use of drugs aiming at these targets in clinical practice are scarce [12].…”
Section: Salivary Duct Cancer (As Example)mentioning
confidence: 99%